Analysis of the relationship between the response to methotrexate therapy and its pharmacokinetic parameters in rheumatoid arthritis. Sovremennaya Revmatologiya - G. I. Gridneva; Yu. V. Muravyov; S. I. Glukhova; E. S. Aronova; E. Yu. Samarkina; N. V. Baimeeva (Современная ревматология, 2022)
The development of therapeutic drug monitoring of methotrexate (MT) remains an important and unresolved problem.Objective: to study the dynamics of the concentration of MT metabolites in groups of patients with different responses to MT therapy, to identify the clinical features of these groups.Patients and methods. The study included 79 patients with rheumatoid arthritis (RA), including 65 (82%) women and 14 (18%) men (mean age 53±11 years). MT monoglutamate was measured in erythrocytes (ER) and mononuclear cells (MO), as well as the main MT metabolites: polyglutamates with 2, 3 and 4 glutamate residues (MTPG2-4), as well as 7-hydroxymethotrexate (7-OH-MT) after 4, 12, 24 and 36 weeks after the start of MT treatment.Results and discussion. Among the patients who completed the 24-week follow-up, 34 responded to MT therapy (Group 1) and 36 did not respond to it (Group 2). Patients of the two groups did not differ in the concentration of various metabolites of MT after 4 weeks, age, body mass index, duration of RA, DAS28 value, radiological stage, functional class, presence of extra-articular manifestations, single and cumulative doses of MT. In the 1st group after 12 weeks of therapy, a higher concentration of 7-OH-MT (ER) was detected, after 24 weeks – a higher concentration of 7-OH-MT (MO) and a lower level of MTPH3 (ER).Conclusion. The concentration of 7-OH-MT after 12 and 24 weeks of therapy was higher in the group of patients who responded to therapy. 7-OH-MT appears to be a more persistent metabolite of MT and therefore more applicable for therapeutic drug monitoring of MT. The level of MT and its metabolites (MT monoglutamate, MTPG2 and 7-OH-MT) gradually decreases over time in responders to therapy. A 7-OH-MT concentration of 14.5 nmol/l may be a predictor of a good response to MT therapy.